2020
DOI: 10.1111/jocn.15586
|View full text |Cite
|
Sign up to set email alerts
|

Nursing Students’ Knowledge, Competence and Attitudes towards Vital Signs Monitoring during Clinical Practice

Abstract: Aim and Objective This study assessed the perceived knowledge and competence, and the attitude of Saudi nursing students towards vital signs monitoring for detecting patient deterioration during clinical rotation. It also examined the predictors of students’ attitudes. Background One of the most important uses of vital signs monitoring is the early detection of deterioration. Vital signs monitoring is one of the most frequently assigned tasks to students during clinical rotation. However, the attitudes of nurs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
10
0
6

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 24 publications
2
10
0
6
Order By: Relevance
“…The scenarios included i) a nurse monitoring a patient’s heart rate; ii) a nurse monitoring a patient’s blood pressure and iii) a nurse motoring a patient’s temperature. Throughout the undergraduate years of training, the most frequently assigned task for nursing students is to monitor a patient’s physiological vital signs in numerous clinical disciplines [ 31 ]. Nurses are required to determine the patient’s condition by means of measuring and interpreting patient’s vital signs.…”
Section: Methodsmentioning
confidence: 99%
“…The scenarios included i) a nurse monitoring a patient’s heart rate; ii) a nurse monitoring a patient’s blood pressure and iii) a nurse motoring a patient’s temperature. Throughout the undergraduate years of training, the most frequently assigned task for nursing students is to monitor a patient’s physiological vital signs in numerous clinical disciplines [ 31 ]. Nurses are required to determine the patient’s condition by means of measuring and interpreting patient’s vital signs.…”
Section: Methodsmentioning
confidence: 99%
“…Literaturni podaci ukazuju na nekoliko izazova u vezi sa vitalnim znacima i drugim metodama fizičke procene pacijenata koje su sprovodili studenti zdravstvene nege (4). Tako je studija sprovedena u Južnoj Africi (5) pokazala da studenti zdravstvene nege imaju poteškoća da identifikuju rane znake pogoršanja stanja pacijenata na osnovu procenjenih vitalnih znakova.…”
Section: Uvodunclassified
“…1031–1032). It is important to emphasize the essential role of nursing students in recognizing the dynamic and changing nature of a patient's condition in addition to vital sign derangement and observations (Alshehry et al., 2020 ). Previous research has indicated that junior medical staff and students have significant shortfalls in recognizing and rescuing deteriorating patients on time, making this an important healthcare education issue (Leonard & Kyriacos, 2015 ; Redfern et al., 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…1031(Jones et al, -1032. It is important to emphasize the essential role of nursing students in recognizing the dynamic and changing nature of a patient's condition in addition to vital sign derangement and observations (Alshehry et al, 2020). Previous…”
mentioning
confidence: 99%